Practicing Philosophy Part of Living Quran: An Initial Survey on Prophet Muhammad as the “Philosopher King” - Mohamed Eusuff Md Amin; Ahmed Al Farisi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This article illustrates the subtle relationship between philosophy as a culture and practice and its timelessness relationship with the Quran as per the Islamic faith. Since the notion of the Quran itself is inseparable from Prophet Muhammad, we propose, that in the world of philosophy, either correct or incorrect, Prophet Muhammad is the “philosopher-king” whom the philosophers, from ancient Greece to modern days, were and are seeking; whether or not they were aware of this reality. Generally in contemporary Muslim experience, philosophy is taken as a subject separate from the Quran. They have disregarded that the source of philosophy, minus the doctrines, is wisdom, and such wisdom, theoretically, could not be separated from the Quran constituting the source of wisdom itself. In this article, we articulate how (i) pre-Islamic Arabia was exposed to different ideas including Hellenistic ones, and how all these human experiences prepare humans to accept the coming of the Last Prophet constituting the Walking Quran. Following the Prophet, his heirs, the scholars of Islam who are the Saints, walk among us; and (ii) studying philosophy helps us recognize them, as they are the wisest amongst us who understood contemporary challenges and provided the intellectual and spiritual leadership for the ‘ummah. If we successfully articulate these two points, we will see that studying philosophy is part of the Quranic spirit. Therefore, we are courageous enough to say that the philosophy world, including its anti-theistic aspects, is not separated from the reality of the Quran (i.e. the Quran recognizes them, and deny them). The qualitative method used in this article started with the proposition that the purpose of studying philosophy is to recognize the “philosopher king” – a proposition we found to be unique. We found the proposition fits the pattern of philosophy development in world history, and we found its pinnacle answer in Prophet Muhammad. This method contributes to the science of qualitative analysis related to the importance of abstract reasoning with empirical facts to formulate a new understanding or narrative. In contemporary Quranic studies, this paper is a reminder that the Quran is not a separate (physical) document from the spiritual realities of every individual, regardless they were Muslims or not,. Therefore, it must not be viewed as merely an external manual to the Muslims, as if, it must be subjected to scrutiny in the interpretations, implying that Quran has to be flexible in order to be timeless. The Quran is the statement of our reality. It is not flexible as determined by factors in time and space. Its timelessness is proven in itself by being not contradictory to human reason, regardless in what society and period they are in. Our proposal is an improvement in the current understanding of “Living Quran” as accepted by contemporary academics.